CHARACTER DEVELOPMENT OF STUDENTS THROUGH THE LEARNING OF ENGLISH MARITIME - Titim Eliawati; Dina Irmayanti Harahap (Universitas Potensi Utama, 2019)
The integration of learning in the classroom with character education is the main agenda of the Indonesian Ministry of Education and Culture. The development of learning methods in the classroom integrated with character education is a challenge for teachers today. Various researches on the development of character education have been carried out, but no one has specifically analyzed the integration of character education in Maritime English learning. The purpose of this study is to increase a top to bottom comprehension of character improvement as seen from the development of learning methods that have been integrated with character values. The research used is qualitative. The method used in this research was classroom action research (CAR). The conclusion from the results of this study is the improvement of the character of students in the classroom in Maritime English learning can be done by choosing the right learning method. On the other hand, the material in the syllabus and lesson plan (RPP) is very helpful for the teacher in arranging the methods, discussions, strategies and learning media needed while in the classroom. Students gave positive respond to changes in learning and learning methods used by teachers.